Cidade caminhante: escritas urbanas e outras feituras com imagens no Centro de Fortaleza/CE - Sá, Alice Diógenes Olímpio Dote (2020)
In the anthropological work with the city, the path is made when walking. Nomadic images attract me, which mobilize and are mobilized by the movement: urban writings (phrases and words that slide across city surfaces in graffiti, stencils, wheat-paste). The collective Narrativas Possíveis, created in 2017 in Fortaleza/CE, put us in pursuit of these images, which, in turn, caused us to perceive and think the city through them. The collective's practices were transmuted and confused with those of this anthropological research, which seeks to encounter urban writings in the Center of Fortaleza/CE through walking. Realizing their movement impelled me to adopt research methods that consider the ways in which they exist and make themselves visible. Inhabiting the in-betweens, therefore, is a matter of “object” and method. Walking-finding-photographing was a trigger for other encounters: the contamination by which the city proceeds produced my desire to relate to it in other ways, such as through audiovisual and drawing, as well as intervening on its surfaces. Thus, I understand the image not only as an “object”, nor as a “representation”, but as a production. Images discoverers and makers, we invent ways of drawing and recreating the city by inhabiting it, with anthropological production itself being one way of this creation. Among the multiple spellings of urban writing, photography, audiovisual, drawing, intervention, a combination of methods-tactics was created, characterizing a doing with images, an anthropological “inventionatic”. I also feel these languages, experimenting the in-between again and discovering something in their folds. For this reason, by operating a “montage” between them, another surface for sharing research emerged, like a table of images where they show themselves in their relationships: cidadecaminhante.tumblr.com. This dissertation, on the one hand, shares this path of research/involvement in and with the city through anthropological work. On the other hand, through the concrete experiences of walking, we think about the ways in which urban writings are exercised, happen, operate in the city. Screams of protest, love messages, intimate outbursts, loose words and even phrases with no apparent meaning: more than the message conveyed in urban writings, the gesture that creates them and is present in them matters. Inhabiting a zone of indiscernibility between art, vandalism and politics, they seem to confuse and desecrate such notions, as well as the normative prescriptions of space, while passing through the daily tracing of paths and affections. The encounters with such images give us the opportunity to think about the mixture; the readability that confuses; the anonymity and co-authorship of those who see (and sometimes scratches the scratches); the game between visibility and invisibility; the ephemerality and the offal; the wandering; the repetition in space and time; the survival of the images. Going through such questions, we also propose that urban writings configure an urban act of micropolitical potency. Realizing the relationship between what urban writing does and what it says, we understand that what is at stake in these images is not only what is written, but the gesture itself, contained in the trail and prolonging it, of writing (in) the city